PREDIKSI KEBANGKRUTAN DI PT. ARGO PANTES TBK TANGERANG - Deharani Nawastari; Arief Rachmawan Assegaf (Jurnal Ekonomi dan Industri, 2022)
The purpose of this study was to determine how the company's financial condition for the period 2012-2021 and predictions of bankruptcy at PT. Argo Pantes Tbk in 2022. The method used in this research is descriptive statistical analysis method using Altman z-score analysis method. The results show that the financial condition of PT. Argo Pantes Tbk during the period 2012-2021, has a bad financial condition, this is based on the company's average ratio of 0 and some ratios are negative. The results of the "Z" analysis show a negative value each year, , it means that the company is in a distress or unhealthy zone. So that the bankruptcy of PT. Argo Pantes Tbk in 2022 can occur in view of the company's poor financial condition and will worsen if the company does not immediately improve its financial health condition.